Views of Thought Islamic Politics of Muhammad Abduh - Aji, Wahyu Trisno (Cognitionis Civitatis et Politicae, 2024)
This research reviews the profile and political thoughts of Muhammad Abduh, a thinker, theologian and reformer of Islamic reform in Egypt at the beginning of the 19th century. Even though he was born in 1849 AD / 1265 AH, the date and year of Muhammad Abduh's birth are not known for certain because of his family's habit of not prioritizing recording. He grew up as a farmer and experienced early education in memorizing the newspaper. Abduh supports democracy and the establishment of laws that are in line with Islamic values. He emphasized the need to limit power with a constitution and detailed the principles of democracy and the establishment of separate but cooperative government institutions. In his view, the government must provide citizens' rights, listen to criticism, and maintain the welfare of society. This research describes the life journey, political thoughts, and contribution of Muhammad Abduh in formulating a moderate view of social and political change in the Islamic world during his time.